The Effect of Brand Origin on Trust in Advertisement and Attitudes towards Advertisement: The Roles of Consumer Ethnocentrism, Cosmopolitanism and Xenocentrism - Selahattin Onur Karlık; V. Özlem Akgün; Tuğçe Sancı (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
In an environment of intense change, where the boundaries of marketing are expanding day by day, trust and loyalty towards brands affect the success of brands. There may be sociological factors underlying this sense of trust. It is important to examine these sociological elements in order to make marketing activities customer-oriented, as required by the new age. In this context, the main purpose of this study is to examine the role of consumer ethnocentrism, xenocentrism, and cosmopolitanism -which are sociology-based concepts- in the effect of brand origin on attitude towards advertisement and trust in advertisement. For this purpose, a 2x2 between-subjects experimental design was established in the study. Therefore, data were collected from 237 undergraduate students via two separate surveys, which included two different advertisement images emphasizing Turkey and France origins. According to the results of the study, perceived inferiority -which is one of the dimensions of consumer xenocentrism- and consumer ethnocentrism have a moderating effect on the relationship between brand origin, attitude towards advertisement, and trust in advertisement. However, results also show that consumer social aggrandizement -one of the dimensions of consumer xenocentrism- and consumer cosmopolitanism do not moderate the aforesaid relationship. It is expected that the study will make theoretical and practical contributions.